Renaissance Influence on Post Byzantine Panel Painting in Crete - Vocotopoulos, Panayotis (Actual Problems of Theory and History of Art, 2016)
During the 15th–17th centuries the Greek island of Crete, then a Venetian colony, developed a school of painting stemming from the Palaeologan tradition but enriched by stylistic and iconographic elements taken from the Italian Renaissance. The paper examines the channels by which Italian features were absorbed by Cretan painters, the importance of these features which varied from painter to painter and from period to period, the dogma to which the artists belonged, nationality and social status of sponsors, the geographical area where Cretan works were exported, new subjects adopted by Post-Byzantine artists, the framing of paintings, and several other aspects of this re ned art which vanished with the Conquest of the island by the Ottomans in the late 17th century.
Keywords: postbyzantine painting; panel painting; Crete; Renaissance influence